2011
DOI: 10.1017/s003329171100287x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of information sources about mental disorders: a comparison of Wikipedia with centrally controlled web and printed sources

Abstract: The quality of information on depression and schizophrenia on Wikipedia is generally as good as, or better than, that provided by centrally controlled websites, Encyclopaedia Britannica and a psychiatry textbook.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 25 publications
0
65
0
3
Order By: Relevance
“…The participatory model, having majority health specialists [45] but also laypeople of varying editorial skills contributing to the health-related content [46], generates high-quality information. Wikipedia was recommended as an appropriate source of information [22,47].…”
Section: Medical Informationmentioning
confidence: 99%
“…The participatory model, having majority health specialists [45] but also laypeople of varying editorial skills contributing to the health-related content [46], generates high-quality information. Wikipedia was recommended as an appropriate source of information [22,47].…”
Section: Medical Informationmentioning
confidence: 99%
“…Reportedly, online resources are more up-to-date than textbooks. [14] An app can simplify the access to relevant state of the art information. [15] These benefits are reflected in the presence of apps for topics that require detailed information, such as disease diagnosis and management or drug references, which have been found to be commonly used among students in Germany and the UK.…”
Section: Interpretation Of the Study Results In Relation To Existing mentioning
confidence: 99%
“…A peer-reviewed 2012 study published in Psychological Medicine found that -the quality of information on depression and schizophrenia on Wikipedia is generally as good as, or better than, that provided by centrally controlled websites, Encyclopaedia Britannica and a psychiatry textbook‖ [23]. A peer-reviewed 2013 study published in Seminars in Dialysis found that -Wikipedia is a comprehensive and fairly reliable medical resource for nephrology patients that is written at a college reading level‖ [24].…”
Section: B Scholarly Studies Of Wikipedia's Credibilitymentioning
confidence: 99%